ISOLATION OF FLAVONOID COMPOUND FROM IRAQI AWSAJ PLANT (LYCIUM BARBARUM L.) FRUITS AND THE STUDY OF ITS ANTIBACTERIAL ACTIVITY - Alassadi, Iqbal J.; Sabah, Fatima S.; Alrubaie, Leaqaa A. (European Scientific Journal, ESJ, 2015)
This study was performed to evaluate the in vitro antimicrobial activity and the flavonoid content of Iraqi awsaj plant (Lycium barbarum L.) fruits. The fruits extracts contain important amounts of flavonoids. The results obtained in the antimicrobial tests revealed that flavonoid compound was more active than alcoholic extract both for Gram-positive and Gram-negative bacterial strains. The results suggest that these species are valuable sources of flavonoids with relevant antimicrobial activities.